Phase behaviour study of swiftlet nest using virgin coconut oil with non-ionic surfactants - Abd Gani, Siti Salwa; Adisah, Siti Zulaika (Malaysian Society of Analytical Sciences, 2015)
Virgin coconut oil (VCO) is the oil that obtained from fresh and mature kernel of the coconut by mechanical or natural means with or without the application of heat, which does not lead to alteration of the nature of the oil. It have advantages such as strengthens the immune system because of its lauric acid content. It also has medium-chain fatty acids which heighten metabolism and energy, thus stimulating the thyroid. Swiftlet nest as an active ingredient need to be dispersed in a carrier system. Thus, ternary phase diagrams were constructed to find the suitable and stable system for it. The phase behavior of systems has been investigated by constructing ternary phase diagrams consisting of non-ionic surfactants/VCO:bird nest/water. The surfactants used were Sorbitan tri-oleate (Span 85), Sorbitan mono-oleate (Span 80), Sorbitan monolaurate (Span 20), Polyoxyethylene(20) sorbitan tri-oleate (Tween 85) and Polyoxyethylene (20) sorbitan mono-oleate (Tween 80). These systems include several phase regions such as homogeneous, isotropic, two-phase and three-phase regions. Different hydrophilic lipophilic balance (HLB) value of non-ionic surfactants exhibit different ternary diagram characteristics. A lower HLB shows a more oil-soluble and a more water-soluble surfactant (larger homogeneous and isotropic region in ternary phase diagrams) whereas high value of HLB shows the reverse of that result. The results show that the T85/VCO:bird nest/water system gave better performance than the other four individual surfactant systems. As a conclusion, high hydrophilic lipophilic balance (HLB) values of surfactant were found to be a good surfactant for the formulation of VCO:bird nest emulsion for cosmetic and pharmaceutical purposes.